Pengaruh Motivasi, Disiplin Kerja Dan Kompensasi Terhadap Produktivitas Karyawan Pada Ramayana Agro Mandiri - Erlina Rizki Fahriza; Muhammad Ridwan Basalamah; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of motivation, work discipline and compensation on employee productivity at Ramayana Agro Mandiri. The data used in this study used primary data through distributing questionnaires to respondents and secondary data to determine the monthly production capacity carried out by Ramayana Agro Mandiri employees. The population in this study were employees of Ramayana Agro Mandiri, while the sample in this study consisted of 38 respondents who were all employees of Ramayana Agro Mandiri. The data analysis method used in this study is multiple linear regression analysis, using the SPSS 25 analysis tool. and compensation partially affect employee productivity. Keywords: Motivation, Work Discipline, Compensation, Employee Productivity